DEVELOPING AN ISLAMIC HUMAN RESOURCE MANAGEMENT MODEL TO ENHANCE TEACHER PERFORMANCE THROUGH SPIRITUAL LEADERSHIP, DIGITAL COMPETENCY, AND ISLAMIC ORGANIZATIONAL CULTURE - Suhardi M Anwar; Hadi Pajarianto; Harun Alrasyid; Elva Amrin (Institut Agama Islam Al Hidayah Bogor, 2026)
Digital transformation in education requires Islamic educational institutions to develop human resource management (HRM) systems that integrate Islamic values, spiritual leadership, and digital competency. Teachers as strategic educational assets require not only professional competence but also technological adaptability and internalization of Islamic organizational values. This study aims to develop an Islamic Human Resource Management (IHRM) model to enhance teacher performance through spiritual leadership, digital competency, and Islamic organizational culture. A quantitative approach with an explanatory research design was employed. The respondents consisted of 119 teachers from Islamic schools, Madrasah Tsanawiyah (MTs), and Madrasah Aliyah (MA) in Palopo City, Indonesia. Data were collected using a five-point Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The results indicate that spiritual leadership and digital competency have positive and significant effects on IHRM and teacher performance. Teacher performance also significantly mediates the effects of spiritual leadership and digital competency on IHRM. However, Islamic organizational culture does not demonstrate a significant direct effect on IHRM and teacher performance. This study develops an IHRM conceptual model that integrates spiritual, digital, and Islamic value dimensions as strategic approaches to improving teacher performance in Islamic educational institutions.